Rethinking Schumann - Kok, Roe-Min; Tunbridge, Laura (New York Oxford University Press, 2011)
A provocative re-examination of a major romantic composer, Rethinking Schumann provides fresh approaches to Schumann's oeuvre and its reception from the perspectives of literature, visual arts, cultural history, performance studies, dance, and film. Traditionally, research has focused on biographical links between the composer and his music, encouraging the assumption that Schumann was solitary, divorced from reality, and frequently associated with "untimeliness." These eighteen new essays argue from a multitude of perspectives that Schumann was in fact very much a man of his time, informed not only by music but also the culture and society around him. The book further reveals that the composer's reputation has been shaped significantly by, for example, changes in attitudes towards German romanticism and its history, and recent developments in musical scholarship and performance. Rethinking Schumann takes into account cultural and social-institutional frameworks, engages with ongoing and new issues of reception and historiography, and offers fresh music-analytical insights. As a whole, the essays assemble a portrait of the artist that reflects the different ways in which Schumann has been understood and misunderstood over the past two hundred years. The volume is, in short, a timely reassessment of this ultimately non-untimely figure's legacy.While the essays consider some of Schumann's most famous music (Dichterliebe, Kinderszenen and the Piano Quintet), they also provide crucial adjustment to judgments against the composer's later works by explaining their musical features not as the result of diminishing creative capacity but as reflections of the political and social situations of mid-nineteenth-century German culture and technological developments. Schumann is revealed to have been a musician engaged by and responsive to his surroundings, whose reputation was formed to a great extent by popular culture, both in his own lifetime as he responded to particular poets and painters, and later, as his life and works were responded to by subsequent generations.FeaturesNew emphasis on Schumann as engaged with popular, political and visual cultureFocus on the often-neglected late works of the late 1840s and early 1850sFeatures Interdisciplinary approachesContributions from the lead scholars in several fields
Robert Schumann and the Culture of German Nationhood / Celia Applegate -- Organizing German Musical Life at Midcentury: Brendel, Schumann, and the Leipzig Tonkünstlerversammlungen and Tonkünstlerverein / James Deaville -- The Cry of the Schuhu: Dissonant History in a Late Schumann Song / Susan Youens -- Segregating Sound: Robert Schumann in the Third Reich / Lily E. Hirsch -- At the Interstice between "Popular" and "Classical": Schumann's Poems of Queen Mary Stuart and European Sentimentality at Midcentury / Jon W. Finson -- Who Was Mignon? What Was She? Popular Catholicism and Schumann's Requiem, Op. 98b / Roe-Min Kok -- Entzückt: Schumann, Raphael, Faust / Nicholas Marston -- Schumann and Agencies of Improvisation / Dana Gooley -- Schumann's Melodramatic Afterlife / Ivan Raykoff -- Meter and Expression in Robert Schumann's Op. 90 / Harald Krebs -- Hypermetric Dissonance in the Later Works of Robert Schumann / William Benjamin -- Associative Harmony, Tonal Pairing, and Middleground Structure in Schumann's Sonata Expositions: The Role of the Mediant in the First Movements of the Piano Quintet, Piano Quartet, and Rhenish Symphony / Peter H. Smith -- Schumann and the style hongrois / Julie Hedges Brown -- Intermediate States of Key in Schumann / David Kopp -- Choreographing Schumann / Wayne Heisler Jr. -- The Fictional Lives of the Schumanns / David Ferris -- Deserted Chambers of the Mind (Schumann Memories) / Laura Tunbridge -- Late Styles / Scott Burnham
Keywords: Schumann, Robert -- 1810-1856; 19th Century (1801-1900); Composer; Biography; Musical analysis; Cuckoo; Germany